Reinterpretasi Ayat al-Qi¡ QS. Al-Baqarah: 178-179 - Akhmad Sulaiman (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
Application qiá¹£Äá¹£ as one of Islamic law is obligatory like SyÄfiâ€™iyahâ€™s and Hanafiyahâ€™s view moreover Khawarij consider the government kafir if they do not apply Islamic law. In fact, qiá¹£Äá¹£ is not applied in every country in which Moslems live, including Indonesia. The aim of this research is reinterpretation ayat al- Qiá¹£Äá¹£ QS. Al-Baqarah 178-179 with the maqÄá¹£id al-syarÄ«ahand socio-histories approach and its implication for Indonesia criminal law. The result of this research is that qiá¹£Äá¹£ is wasÄ«lah to achieve á¸¥ifáº“ al-nafs aim. Qiá¹£Äá¹£ choice as wasÄ«lahis influenced Arab civilâ€™s tradition before Islam. Because of it, qiá¹£Äá¹£as wasÄ«lah can be changed by Indonesia criminal law that is written in article 338, 339, 340 and 344 KUHP